1981
DOI: 10.1530/jrf.0.0620099
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen concentrations in systemic plasma of pregnant pygmy goats

Abstract: Concentrations of oestradiol-17 beta, oestradiol-17 alpha, and oestrone in systemic plasma of pregnant pygmy goats (Capra hircus) remained low until about Day 60 and then rose to maximum values at Days 120-140 (parturition Day 140-145). Oestradiol-17 alpha was the predominant oestrogen. All 3 oestrogens at Days 100-130 were higher in females carrying 3 fetuses than in those carrying only one, but at Days 70-90 only oestrone values were higher. It is suggested that the feto-placental unit is the source of oestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…The present finding showed higher level (over all 11.59% higher) of estrogen in twin pregnancy as compared to singlet on all test days although it was not significant. Dhindsa et al (1981) also reported significantly higher estradiol in goats with multiple fetuses as compared to singlet fetus. Moreover Manalu et al (1996) reported two times higher concentration of estrogen in twin bearing goats as compared to singlet bearing goats.…”
Section: Plasma Hormonesmentioning
confidence: 84%
“…The present finding showed higher level (over all 11.59% higher) of estrogen in twin pregnancy as compared to singlet on all test days although it was not significant. Dhindsa et al (1981) also reported significantly higher estradiol in goats with multiple fetuses as compared to singlet fetus. Moreover Manalu et al (1996) reported two times higher concentration of estrogen in twin bearing goats as compared to singlet bearing goats.…”
Section: Plasma Hormonesmentioning
confidence: 84%
“…In normally cycling Shiba goats, the concentrations of E 2 -17β at estrus [14, 15, 17] were reported to be approximately 20–30 pg/ml. In pregnant goats approaching parturition, it was reported that the concentration of E 2 -17β in maternal circulation reaches maximally 10-fold as much as that at estrus, while estrone and estradiol-17α become 10- to 15-fold higher than E 2 -17β [28,29,30,31,32,33,34]. Studies in sheep [35], humans [36, 37] and rats [36] suggested that estrone and estradiol-17α have about 20–60% binding affinities to estrogen receptors relative to E 2 -17β.…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated the ability of a hormone-based test to detect non-pregnancy where it might otherwise have gone undetected. Dhindsa, Metcalfe & Resko (1981) have examined oestrogen levels by RIA in goats during pregnancy but the specific steroids were oestrone, oestradiol-17a and oestradiol-17ß and they were examined in circulating plasma as opposed to milk. They found that levels of oestrogens were significantly higher in the plasma of pregnant animals carrying multiple fetuses than in plasma from animals with a single fetus.…”
Section: Discussionmentioning
confidence: 99%